A telekárak és a demográfiai mutatók Bács-Kiskun megye térszerkezetében - Tánczos-Szabó, László (Közép-Európai Közlemények, 2009)
The commercial value of real property is to be considered a major characteristic of any particular segment of the broader socio-economic structure. With the prevalence of market economy, prices of tenements have turned into a determining factor of space-structure in minor settlements as well as major cities and metropolises. As for the potential utilisation of the environment, it is not insignificant that there is an underlying value-judgement beyond the divergence of prices. It is for this reason that we have decided to draw up a map of real-estate prices that covers both the inner parts and the peripheries of all the settlements in Bács-Kiskun County. From the outcome of this research – e.g., the resulting outlines of various sectors – the conclusion can be drawn that real-estate prices can be used effectively in regional research projects. Social factors have accentuated roles, beside economic factors, in space-structure analyses. In this short study we are trying to show how the picture drawn by demographic indicators is related to the map of real-estate prices in the county.